TINJAUAN YURIDIS PERJANJIAN JUAL-BELI TENAGA LISTRIK ANTARA PT PLN DENGAN PELANGGAN - Denny Ardian Priambodo (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractIncreasingly diverse electricity needs make the government obliged to make proper arrangements in the implementation of electrical energy distribution, so the government needs to appoint a State-Owned Enterprise (BUMN) named PT. The State Electricity Company which is often referred to as PT. PLN (Persero). PT PLN (Persero) as the electricity manager appointed by the government continues to improve in providing services to the community until now PLN continues to strive to meet people's needs for electricity by issuing various existing electrical service products, it is hoped that the need for electrical energy in Indonesia can be fulfilled to the maximum. maybe. Problems that occur in subscribing to electricity, both technically and administratively, are most often carried out by the community through the services of third parties (installers registered with PLN and installers who are not registered with PLN), because they want to get fast service. As a result, in addition to the high costs due to installers asking for additional services, people are also often victims because the expected fast service is also not fulfilled and there is a lot of public electricity supply that is not registered or not officially at PLN (Illegal). In practice, PT PLN as a provider of electricity in accordance with the mandate of Law No. 8 of 1999 concerning consumer protection is obliged to provide clear information on traded goods or services.